2005
DOI: 10.1007/s11064-005-8802-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Cannabinoid-1 Receptor Upregulation Upon Endothelin-B Receptor Deficiency: A Neuroprotective Substitution Effect?

Abstract: Endothelin (ETB)-receptors mediate anti-apoptotic actions. Lack of functional ETB-receptors leads to increased neuronal apoptosis in the hippocampus. The increased apoptosis must be compensated by other mechanisms, however, as ETB-deficient rats display normal overall brain morphology. To illuminate on brain plasticity in ETB-receptor deficiency, we studied the expression and function of another neuroprotective system, the cannabinoid CB1-receptors, in ETB-deficient hippocampus. We show that CB1 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our data are in agreement with a transient protection hypothesis for the endocannabinoid system; we observed a peak of CB 1 expression after 7 days of survival time in visual structures. Several studies indeed demonstrate increased levels of endocannabinoids and up-regulation of CB 1 receptors in brain injury models in rats and mice (Romero et al, 2000;Hansen et al, 2001;Panikashvili et al, 2001;van der Stelt et al, 2001;Unzicker et al, 2005). For example, Hansen and collaborators (2001), using rats with mild neurodegenerative processes induced by changes of glutamatergic neurotransmission and of endocannabinoid homeostasis, found higher levels of anandamide, but not of 2-AG, and increased binding and mRNA of CB 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are in agreement with a transient protection hypothesis for the endocannabinoid system; we observed a peak of CB 1 expression after 7 days of survival time in visual structures. Several studies indeed demonstrate increased levels of endocannabinoids and up-regulation of CB 1 receptors in brain injury models in rats and mice (Romero et al, 2000;Hansen et al, 2001;Panikashvili et al, 2001;van der Stelt et al, 2001;Unzicker et al, 2005). For example, Hansen and collaborators (2001), using rats with mild neurodegenerative processes induced by changes of glutamatergic neurotransmission and of endocannabinoid homeostasis, found higher levels of anandamide, but not of 2-AG, and increased binding and mRNA of CB 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated increased levels of endocannabinoids and up-regulation of CB 1 receptors in brain damage models in rats and mice (Romero et al, 2000;Hansen et al, 2001;Panikashvili et al, 2001;van der Stelt et al, 2001;Unzicker et al, 2005). The observed accummulation of endocannabinoids and CB 1 up-regulation could represent a protective response contributing to rescue neurons from death.…”
mentioning
confidence: 97%
“…The CB 1 receptor is ideally located to regulate neural cell fate decisions as it is present along the neural lineage from progenitor to differentiated cells (9,23), its expression increases after injury in various in vivo models (37,38), and its activation regulates neural cell survival and proliferation (11,12), migration, and axonal growth (23). In addition, the synthesis of the endogenous ligands AEA and 2AG is increased after different types of brain insults including excitotoxicity and during neuronal activity (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown by using this method that at day 6 in culture rat hippocampal neurons grow extended neuronal processes, express markers for mature neurons (MAP-2, NF-200), display high vulnerability to hypoxia and show less than 10% contamination with astrocytes [23,[27][28][29]. Briefly, hippocampi were removed, digested with solution containing papain and DNAse and subjected to density gradient centrifugation.…”
Section: Primary Hippocampal Neuronal Culturesmentioning
confidence: 99%